The Comparison of Zakat Utilization in Muslim Minority and Majority Country - Irma (SMART Insight, 2021)
This study aims to compare the categorization of asnaf and the utilization of zakat funds by zakat institutions in Muslim minority countries and Muslim majority countries. The Muslim minority country which is the subject of the research is Thailand, which is represented by the Sattachon Thailand Foundation, as the oldest zakat institution in Bangkok. Meanwhile, Muslim-majority countries are represented by Indonesia through Dompet Dhuafa, Brunei Darussalam through the Islamic Ulema Council of Brunei Darussalam, and Malaysia through Baitul Mal Malaysia. The method used is the Field Research and Library Research methods which are descriptive qualitative. In collecting data using the method of observation, interviews, and documentation. The results showed: (1) The Sattachon Foundation distributed zakat funds to all categories of asnaf, namely the indigent, the poor, amil, converts, riqab, gharim, fi sabilillah, and ibn sabil. The distribution pattern used is traditional consumptive and creative consumptive. (2) There are differences in interpreting the eight asnaf who are entitled to receive zakat, thus causing differences in the implementation of the distribution of zakat funds. The Sattachon Foundation and the Baitul Mal Majlis of the Malaysian Islamic Religion Association (MAIWP) distributed it to all asnaf. Dompet Dhuafa Indonesia distributes to all asnaf groups except riqab. Meanwhile, the Brunei Darussalam Islamic Religious Council (MUIB) does not distribute to asnaf riqab and fi sabilillah. Meanwhile, the distribution pattern applied at the Sattachon Foundation is lagging behind when compared to Dompet Dhuafa Indonesia, Majlis Ulama Islam Brunei Darussalam, and Baitul Mal Malaysia.